Proceedings of the International Conference on Nanomedicine (ICON-2019) - Rajan, Mariappan; Anand, Krishnan; Chuturgoon, Anil (Springer Proceedings in Materials, 2019)
This book presents the Proceedings of ICON-2019, an international meeting exclusively dedicated to nanostructured materials in medicinal applications. The conference emphasized the recent advances in multidisciplinary research on processing, morphol¬ogy, structure and properties of nanostructured materials and their applications in vari¬ous medicinal fields. The papers encompass basic studies and applications and address topics of novel issues, difficulties, and breakthroughs in the field of nanomedicine in cancer, tuberculosis, tissue engineering, regenerative medicine etc.